Vertebrate Resources (Birds and Mammals) of University Campus at Solan (H.P.) - a Non-protected Area, with Notes on Damage Caused by Them - Narang, M. L. (Indian Forester, 2005)
The studies were undertaken to prepare a database of vertebrate resources (birds and mammals) in an unprotected area of Himachal Pradesh. The studies were undertaken in the Nauni campus of University of Horticulture and Forestry and its surrounding areas in districts of Solan and Sirmour. Systematic survey of various ecosystems of the study area revealed the occurrence of 153 species of birds belonging to 37 families and 14 species of large and medium sized mammals. The mammalian fauna include 2 species of primates, 6 species of carnivores, 4 species of ungulates, a lagomorph and a rodent. Majority of mammalian fauna found in the study area as also in other parts of the state cause damage to crops and plants. Amongst the birds, four species of parakeets and jungle crow are the prominent species causing damage to agricultural and horticultural crops. The fauna of the study area which is a non-protected area is identical to the fauna of nearby Chail Wildlife Sanctuary which is a protected area. There is a need to identify such areas throughout the state and exploitation of natural resources should be restricted in these areas.